MARKETING COMMUNICATIONS FOR WEAVING AS A COMMUNITY-BASED CULTURAL TOURISM DESTINATION (CASE STUDY OF THE SARI BHAKTI WEAVING GROUP BANJAR PESALAKAN, PEJENG KANGIN VILLAGE) - Made Ika Kusuma Dewi; Anggara Putu Dharma Putra (UHN IGB Sugriwa Denpasar, 2025)
Marketing communications for Cagcag weaving, Banjar Pesalakan, can develop into a community-based cultural tourism village. To keep cagcag weaving relevant in the global tourism market, an effective marketing communication strategy is needed. A local community-based approach is the key to creating an authentic and sustainable strategy. This article will discuss how marketing communications for cagcag weaving based on the local community of Pesalakan Banjar Pejeng Kangin Village can strengthen product identity and improve the economic welfare of local communities based on cultural tourism villages. Local community-based cagcag weaving marketing communication is an approach that utilizes the knowledge, skills and uniqueness of local communities to market cagcag weaving products. This approach aims to highlight the authenticity and cultural richness contained in cagcag woven products, especially the gegambir motif, while providing direct economic and tourism benefits to craftsmen and tourists. Cagcag weaving in Banjar Pesalakan, Pejeng Kangin village is a Bhakti sari weaving group. Cagcag weaving in Banjar Pesalakan has characteristics that are different from weaving in general, namely gegambir weaving. Gegambir weaving is a traditional weaving typical of the people of Banjar Pesalakan and can only be found and produced by the Sari Bhakti weaving group originating from Banjar Pesalakan. Gegambir weaving has a cloth width of approximately 20 to 45 cm (maximum 60 cm) and a cloth length of 2 meters. Generally, gegambir weaving is only used as a means of complementing ceremonial clothing, such as being used as a shawl, udeng, and gegambir woven cloth is also used for religious activities, teeth cutting ceremonies or often called mepandes, along with the development of fashion, the development of globalization of tourism and market demand for gegambir weaving which has now changed its function to interior designs such as tablecloths, wall hangings and room decorations as desired. This research is a qualitative perspective. In this qualitative approach, the emphasis is on the depth (quality) of data, not the amount (quantity) of data. The method used is the observation method, case study method and literature method, where in this observation method the researcher directly observes the object under study, namely the cagcag weaving of the Bhakti sari weaving group found in Banjar Pesalakan, Pejeng Kangin village.